Effects of l- and d-arginine on the basal tone of human diseased coronary arteries and their responses to substance P. Issue 5 (1st May 1999) - Tousoulis, D; Tentolouris, C; Crake, T; Katsimaglis, G; Stefanadis, C; Toutouzas, P; Davies, G J
Abstract : OBJECTIVE: To assess the effects of substance P administration alone and in combination withl - and d -arginine in patients with normal angiograms and in patients with coronary artery disease. DESIGN: Intracoronary infusions of (a) normal saline, (b) the receptor mediated nitric oxide stimulant substance P (5.6 and 27.8 pmol/min) before and afterl - or d -arginine (50 and 150 μmol/min), and (c) glyceryl trinitrate (250 μg bolus) were given to 17 patients with coronary artery disease and stable angina, and to six patients with normal angiograms. The diameter of angiographically normal proximal and distal segments and coronary stenoses were measured by computerised quantitative angiography. RESULTS: l -arginine administration was associated with significant dilatation of stenoses (p < 0.01) of proximal segments of both "normal" (p < 0.05) and diseased (p < 0.01) arteries, and of distal segments of diseased arteries (p < 0.01). No significant changes were associated withd -arginine administration. Dose dependent dilatation of all segments including stenoses, was observed with substance P both before and after l -arginine infusion (p < 0.01). The magnitude of dilatation of stenoses and all segments of both "normal" and diseased coronaries was greater after l -arginine (p < 0.05) but not d -arginine and substance P infusion, than it was after saline and substance P infusion. Administration ofd - or l -arginine did not change the magnitude of substance P induced dilatation. CONCLUSIONS: Diseased and "normal" coronary arteries dilated in response to substance P and l -arginine but were unaffected byd -arginine infusion. The magnitude of the response to substance P was not increased by l -arginine administration, indicating that it is not critically dependent on the availability of substrate for nitric oxide synthase.